Bad Company: Supracristal VSD Presenting with Ruptured Sinus of Valsalva Aneurysm. A Case Presentation with Echocardiographic Depiction and an Analysis of Contemporary Literature. Issue 3 (11th August 2014) - Hartlage, Gregory R.; Consolini, Michelle A.; Pernetz, Maria A.; Williams, B. Robinson; Clements, Stephen D.; Chen, Edward P.; Rab, S. Tanveer
<x xml:space="preserve">Abstract</x> Supracristal ventricular septal defect (SCVSD), a defect of the infundibular portion of the interventricular septum just below the right aortic cusp, occurs more frequently in Eastern Asian populations. SCVSD may be complicated by right sinus of Valsalva aneurysm (SoVA). We present the case of a 26‐year‐old male of Korean descent with a history of a childhood murmur who was referred to our institution for progressive heart failure symptoms. He was diagnosed with SCVSD and ruptured right SoVA based on history, physical exam, and echocardiography including three‐dimensional transesophageal echocardiography with reconstructed surgical views. The patient underwent SCVSD closure, SoVA excision, and valve‐sparing aortic root replacement. We reviewed the echocardiography literature regarding SCVSD and SoVA, and analyzed contemporary literature of SoVA and its relationship with SCVSD. We conclude that a higher prevalence of ruptured SoVA in Eastern Asians is likely related to a higher prevalence of underlying SCVSD in this population.